2014
DOI: 10.1371/journal.ppat.1004314
|View full text |Cite
|
Sign up to set email alerts
|

Strain-Specific Properties and T Cells Regulate the Susceptibility to Papilloma Induction by Mus musculus Papillomavirus 1

Abstract: The immunocytes that regulate papillomavirus infection and lesion development in humans and animals remain largely undefined. We found that immunocompetent mice with varying H-2 haplotypes displayed asymptomatic skin infection that produced L1 when challenged with 6×1010 MusPV1 virions, the recently identified domestic mouse papillomavirus (also designated “MmuPV1”), but were uniformly resistant to MusPV1-induced papillomatosis. Broad immunosuppression with cyclosporin A resulted in variable induction of papil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
103
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(115 citation statements)
references
References 50 publications
12
103
0
Order By: Relevance
“…Together, the data show that activation of keratinocytes by IL-15 is sufficient to induce recruitment of neutrophils. Because neutrophils are not thought to be associated with protection against HPV, we tested the response of DCs and CD4 + T cells that are considered to be more relevant during HPV infection (Amador-Molina et al, 2013; Handisurya et al, 2013, 2014; Wang et al, 2015). As seen with neutrophils, the average speed of DC migration in two-dimensional chambers (Figure 5a) was significantly increased using the chemokine cocktail at the concentrations released by IL-15–stimulated control keratinocytes (“scr + IL-15” in Figure 5b–d).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Together, the data show that activation of keratinocytes by IL-15 is sufficient to induce recruitment of neutrophils. Because neutrophils are not thought to be associated with protection against HPV, we tested the response of DCs and CD4 + T cells that are considered to be more relevant during HPV infection (Amador-Molina et al, 2013; Handisurya et al, 2013, 2014; Wang et al, 2015). As seen with neutrophils, the average speed of DC migration in two-dimensional chambers (Figure 5a) was significantly increased using the chemokine cocktail at the concentrations released by IL-15–stimulated control keratinocytes (“scr + IL-15” in Figure 5b–d).…”
Section: Resultsmentioning
confidence: 99%
“…This, however, does not explain why established wart lesions fail to regress in γc-deficiency despite restoration of T-cell immunity that is considered the major factor for immunological control of established HPV infection (Coleman et al, 1994; Handisurya et al, 2014; Knowles et al, 1996; Nicholls et al, 2001; Uberoi et al, 2016; Wilgenburg et al, 2005). …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study has shown that LCs isolated from women with persistent HPV16 infection can present HPV antigens and activate HPV16-specific CD8 + T cells (Da Silva et al, 2015). Additionally, using the recently established mouse papillomavirus (Mus musculus papillomavirus 1 or MmuPV1) model, Handisurya et al revealed that productive MmuPV1 infection and papilloma formation require both CD4 + and CD8 + T cell functions; while CD4- or CD8-knockout C57BL/6 mice were resistant to productive MmuPV infection, depletion of CD4 + and CD8 + T cells from immunocompetent mice led to infection and papilloma formation (Handisurya et al, 2014). In addition, UVB irradiation-induced systemic immune suppression causes mice to become highly susceptible to MmuPV1 infection, which ultimately results in the development of squamous cell carcinoma (Uberoi et al, 2016).…”
Section: Host Defense Mechanisms Against Hpvmentioning
confidence: 99%
“…Most mouse strains are susceptible to infection in which adaptive immunity plays a major role in rapid clearance (Handisurya, Day et al, 2014; Wang, Jiang et al, 2015; Sundberg, Stearns et al, 2014). …”
Section: Preclinical Models (In Vivo)mentioning
confidence: 99%